(3GdeSGFd GdWHQjIs - (3CHh GdbGSe, GdTQja GdeQJVj, Ydj Hf GdMSjf Hf ehSi, J (B436(3g` (B1044(3e(B)s ((3cGTa GdZWGAs)
(3ChdgG (B:s
(3ChdgG(B: (3gPg GdeSGFd GdJj GfJRYgG GdSjO GdeQMhe GdeQJVi ef abg GdfGUQjI (B... (3GdeSFdI GdChdi(B: (3bGd GdfGUQ(B: (3EPG hbYJ GdfLGSIs
(3BNQgG (B:s
(3BNQgG(B: (3ajchf bhdg JYGdi hdCHhjg dcd hGMO efgeG GdSOS eJfGhdGdI hgh NdGa GdELeGY dCfG fbhd gj eJfGhdI dg dcfg aQM HGdELeGYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B4: 278s
(3GdPQjYI, L (B5: 161s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis